Checklists of Parasites Stray Cats Felis Catus of Iraq - Al-Tae, Abdul-Rahman Aziz; Al-Rubaie, Abdul-Razzak L. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The literature reviews of all reports of parasites fauna cats Felis catus in Iraq species of including 15 protozoa (Babesia spp., Crptosporidium spp., C. muris, C. parvum, Cytauxzoon felis, Eimeria cati, Entamoeba spp., Giardia sp., Giardia spp., Isospora ssp., I. felis., I. rivolta, Leishmania tropica and Toxoplasma gondii), five trematoda (Heterophyes aequalis, H. heterophyes, Opisthorchis felineus, O. tenuicollis and Paragonimus killicotti), 17 cestoda (Diphyllobothrium sp., D. latum, Diplopylidium acanthotetra, D. nolleri, Dipylidium spp., D. caninum, D. sexcoronatum, Hydatigera taeniaeformis, Joyeuxiella echinorhyncoides, J. pasqualei, Mesocestoides variabilis, Spirometra sp., S. erinaceieuropaei, S. mansonoides, Taenia sp., Taenia spp. and T. taeniaeformis), 18 nematoda) Aelurostrongylus abstrusus, Ancylostoma spp., A. paraduodenale, A. tubaeforme, Capillaria spp., C. arophilia, C. felis, Dioctophyma renale, Dirofilaria immitis, Ganathostoma sp., Ollulanus tricuspis, Physaloptera praeputiale, Pterygodermatites cahirensis, Rictularia cahirensis, Strongyloides spp., Toxascaris leonine, Toxocara sp. and T. cati) and seven arthropoda (Ctenocephalides felis, Felicola subrostratus, Ixodes spp., Otodectes cynotis, Rhipicephalus sp., R. sanguineus and R. turanicus).